Development of chitosan-graphene oxide nanocomposite films for active margarine packaging - Foong, Han Lyn (2021)
Chitosan (CS) has gained significant attention as a food packaging material due to its film-forming ability, biocompatibility, and biodegradability. However, its applications have been limited by its weak mechanical properties and hydrophilicity. The aim of this study was to develop a chitosan-graphene oxide (CSGO) nanocomposite film with improved mechanical properties as well as water vapour, oxygen, and light barrier properties in comparison to pure CS film, for the antioxidant active packaging of palm olein-based margarine. In the first objective, GO samples with four different degrees of oxidation were synthesized by controlling the ratio of graphite to the oxidizing agent, potassium permanganate (KMnO4). The sample GO4, synthesized with a 1:8 w/w graphite:KMnO4 ratio was embedded with abundant oxygen-containing groups, as supported by the Fourier-transform infrared (FTIR) and Raman spectra. The addition of GO4 into CS increased (p < 0.05) the mechanical strength and UV light barrier of the CS/GO4 composite. In the second objective, the effects of sonication time of GO4 (30, 60, and 120 min) and heating temperature of the films (30, 60, and 120 ºC) on the structural and physical properties of the CSGO4 composites were investigated. After 120 min of sonication in a sonicator bath, graphene oxide nanosheets (GO120) of ~1 nm thick were obtained, as demonstrated using dynamic light scattering (DLS) technique and atomic force microscopy (AFM). The incorporation of GO120 decreased (p < 0.05) the light transmittance of CS films whereas heating the composites at 120 °C lowered (p < 0.05) the water solubility and water vapour permeability (WVP). All of the films were completely decomposed within 28 days in a soil burial test. In the third objective, trisodium citrate (CIT) and sodium tripolyphosphate (TPP) solutions of different concentrations (0.5, 1.0. 2.0, and 3.0% w/v) were used as crosslinking agents for the films. Successful crosslinking was confirmed by FTIR spectroscopy. The hydrophilicity and light transmittance decreased (p < 0.05) with the increase in CIT and TPP. At 3.0% w/v, the elongation at break and tensile strength of the TPP-crosslinked CSGO films increased (p < 0.05) by 42 and 82%, respectively, outperforming CIT as a crosslinking agent. In the final objective, the effect of the concentrations of CS (1.5 and 2.0% w/v) and GO4 (0.5, 1.0, and 2.0% w/w CS) on the properties of nanocomposite films were investigated. The WVP and oxygen permeability (OP) decreased (p < 0.05) by 43 and 54%, respectively. The antioxidant properties of the composite film increased (p < 0.05) with the concentration of GO4, as supported by the DPPH radical scavenging assay. The changes in the peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) of the margarine samples were monitored for 30 d at 4 ºC. For the margarine sample that was wrapped with the GOCS1.5 GO2.0 film (CS 1.5% w/v, GO 2.0% w/w CS), the PV and TBARS values were 36 and 79% lower (p < 0.05) in comparison to the low-density polyethylene films. The combination of these properties such as low WVP, OP, and light transmittance, as well as the radical scavenging activities suggests that the CS1.5 GO2.0 film could be a potential antioxidant active packaging for margarine.